2007
DOI: 10.3892/ijo.30.4.785
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 uses the protein kinase C/ interleukin-8/urokinase-type plasminogen activator pathway to increase the invasiveness of breast cancer cells

Abstract: Abstract. Cyclooxygenase-2 (COX-2) increases breast cancer cell invasion. Expression of various pro-angiogenic and pro-invasive factors has been correlated with high expression of COX-2. However, whether these factors are essential to COX-2-mediated breast cancer invasion, and the mechanisms by which COX-2 increases the expression of these factors are unknown. Our microarray results indicate that higher COX-2 expression was associated with increased levels of interleukin-8 (IL-8), a key factor in breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…The invasiveness of the cells was assessed by Matrigel invasion assays as previously described [6]. Briefly, MCF-7, MCF-7/Vector and MCF-7PDCD4 cells (4 × 10 5 ) were cultured and treated with 10 μM PGE 2 or 100 ng/ml IL-8 for 24 h prior to the invasion assay.…”
Section: Matrigel Invasion Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The invasiveness of the cells was assessed by Matrigel invasion assays as previously described [6]. Briefly, MCF-7, MCF-7/Vector and MCF-7PDCD4 cells (4 × 10 5 ) were cultured and treated with 10 μM PGE 2 or 100 ng/ml IL-8 for 24 h prior to the invasion assay.…”
Section: Matrigel Invasion Assaysmentioning
confidence: 99%
“…High COX-2 expression in breast tumors has been correlated with poor survival, distant metastasis and lower local-regional control of disease [2,3]. Ectopic expression of COX-2 in breast cancer cell lines was found to increase the production of prostaglandin E 2 (PGE 2 ) and interleukin-8 (IL-8), which are essential to COX-2-induced breast cancer invasion [5][6][7]. However, which downstream factors are inhibited by the COX-2/ PGE 2 /IL-8-mediated pathway to induce breast cancer cell invasion are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (34) demonstrated the close interaction between IL-8 and COX-2 in bone metastasis of breast cancer. The correlation between the expression of IL-8 and COX-2 in breast cancer has also been highlighted by numerous studies (34,35), and it has been suggested that IL-8 and COX-2 are mutually regulated to promote the genesis and development of tumor (36). Therefore, the present study hypothesized that propofol may inhibit COX-2.…”
Section: Discussionmentioning
confidence: 58%
“…Simeone et al (2007) reported that high IL-8 expression promotes breast cancer metastasis. In addition to its relationship with angiogenesis, IL-8 is also associated with the metastatic phenotype and it promotes breast tumor cell potential, especially because this area receives a rich blood supply (De Larco et al, 2003;BobrovnikovaMarjon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It acts along with vascular endothelial growth factor (VEGF) and eukaryotic initiation factor (eIF4E) (Zhou et al, 2006). In addition, cyclooxygenase-2 (COX-2) increases the invasiveness of breast cancer through IL-8 activation (Simeone et al, 2007).…”
Section: Introductionmentioning
confidence: 99%